The Effect of Organizational Culture and Communication Skills on Administrative Performance in Higher Education Institutions in East Java - Mohamad Sudi; Ivon Arisanti; Siti Aisyah Hanim; Ridwan Sya’rani; Kusuma Agdhi Rahwana (West Science Interdisciplinary Studies, 2024)
This research investigates the impact of organizational culture and communication skills on administrative performance in higher education institutions in East Java. Utilizing a quantitative approach with a sample of 250 administrative staff, the study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze the relationships among these key variables. The measurement model assessment confirms the reliability and validity of the constructs, while the structural model reveals significant and positive effects of both organizational culture and communication skills on administrative performance. The findings highlight the importance of fostering a positive organizational culture and enhancing communication skills to optimize administrative efficiency. The study contributes valuable insights to the field of higher education administration and offers practical recommendations for institutions seeking to improve their administrative practices.